FT-IR spectroscopic investigation of transition metal (II) 2-aminopyridine tetracyanonickelate complexes - AKYÜZ, SEVİM (Elsevier, 2000)
A series of Hofmann-type clathrate host molecules containing two 2-aminopyridine (2-Apy) groups attached to transition metal (II) (M) tetracyanonickelate frame, with the formula: M(2Apy)2Ni(CN)4 (where M=Mn, Co, Cu or Zn), have been synthesised for the first time. Their FT-IR spectra are reported in the 400–4000 cm−1 region. The spectral features suggest that the compounds are substantially isostructural to that of already known Hofmann type pyridine complex; M(py)2Ni(CN)4. Moreover, 2Apy pyridine molecules are found to involve coordination through the ring nitrogen. The coordination effect on the 2Apy modes was analysed.
Keywords: Infrared spectrometry; Hofmann type complexes; Tetracyanonickelate; Transition metal; Aminopyridine; Pyridine derivatives